Effect of light and media composition on growth and stomatal density of Phalaenopsis amboinensis - MUHAMMAD ALANWARI NUGRAHA; DWI MURTI PUSPITANINGTYAS; HARYANTO HARYANTO (Nusantara Bioscience, 2025)
Abstract. Nugraha MA, Puspitaningtyas DM, Haryanto. 2025. Effect of light and media composition on growth and stomatal density of Phalaenopsis amboinensis. Nusantara Bioscience 17: 243-252. Phalaenopsis amboinensis J.J.Sm. is an endangered orchid species endemic to Indonesia, valued for both its conservation significance and horticultural potential. However, limited natural populations and slow propagation rates hinder sustainable conservation efforts. This study investigated the combined effects of culture media composition and light conditions on the in vitro growth, chlorophyll content, and stomatal density of P. amboinensis plantlets. A factorial experiment was conducted using nine media formulations under light and dark conditions. Significant interactions between media and light treatments were observed across all measured parameters (p < 0.05). The KC EO2 medium, containing 2 g/L KC, 40 g/L potato (Solanum tuberosum L.) extract, 2 g/L peptone, and MS vitamins under light, produced the most vigorous vegetative growth (5.40 ± 2.50 leaves, 1.44 ± 0.31 cm leaf length, 2.00 ± 0.82 roots, and 1.89 ± 0.45 cm root length). In contrast, the KC EO3 medium with 2 g/L KC, 150 g/L mung bean sprout (Vigna radiata (L.) R.Wilczek) extract, and 150 mL/L young coconut water (Cocos nucifera L.) under light yielded the highest chlorophyll a content (0.695 ± 0.113 mg/g fresh weight) and stomatal density (77.57 ± 2.72 stomata/mm²). Control plantlets cultured without organic supplements under dark conditions showed poor growth and negligible chlorophyll accumulation. These findings demonstrate that organic-enriched media, especially when combined with light exposure, significantly enhance physiological and morphological development in vitro. The optimized culture conditions offer a practical and scalable protocol for ex situ conservation and commercial propagation of P. amboinensis, supporting the preservation and sustainable use of this rare orchid species.